2017
DOI: 10.1155/2017/5489523
|View full text |Cite
|
Sign up to set email alerts
|

Significant Improvement Selected Mediators of Inflammation in Phenotypes of Women with PCOS after Reduction and Low GI Diet

Abstract: Many researchers suggest an increased risk of atherosclerosis in women with polycystic ovary syndrome. In the available literature, there are no studies on the mediators of inflammation in women with PCOS, especially after dietary intervention. Eicosanoids (HETE and HODE) were compared between the biochemical phenotypes of women with PCOS (normal and high androgens) and after the 3-month reduction diet. Eicosanoid profiles (9(S)-HODE, 13(S)-HODE, 5(S)-HETE, 12(S)-HETE, 15(S)-HETE, 5(S)-oxoETE, 16(R)-HETE, 16(S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The weight of women suffering from PCOS is also an important factor affecting inflammation intensity, with significantly lower 5-HETE and 12-HETE concentrations among underweight patients compared to obese patients [ 28 ]. Very interesting conclusions were reached by Szczuko et al [ 29 ]. The authors have shown that women suffering from PCOS who have experienced pharmacotherapy have a significantly lower concentration of inflammatory mediators (5-, 12-, 15-, and 16-HETE and 9- and 13-HODE) in their blood when compared to potentially healthy women in a control group.…”
Section: Participation Of Aa Metabolites In Fertilitymentioning
confidence: 82%
“…The weight of women suffering from PCOS is also an important factor affecting inflammation intensity, with significantly lower 5-HETE and 12-HETE concentrations among underweight patients compared to obese patients [ 28 ]. Very interesting conclusions were reached by Szczuko et al [ 29 ]. The authors have shown that women suffering from PCOS who have experienced pharmacotherapy have a significantly lower concentration of inflammatory mediators (5-, 12-, 15-, and 16-HETE and 9- and 13-HODE) in their blood when compared to potentially healthy women in a control group.…”
Section: Participation Of Aa Metabolites In Fertilitymentioning
confidence: 82%
“…32, 34 Moreover, 12-HETE, produced via 12- LOX within the AA cascade, is a potent chemoattractant for neutrophils. 35 In addition, LTB 4 and its isomer trans-LTB 4 stimulate the neutrophil chemotaxis in UC. 36 Furthermore, TXB 2 is the stable downstream metabolite of thromboxane A 2 (TXA 2 ), which is known for causing vasoconstriction, platelet aggregation, and T-cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…The quantification was based on peak areas with internal standard calibration. Quantitative analysis was conducted using ChemStation Software (Agilent Technologies, Cheadle, UK) 44 , 45 .
Figure 3 Analyzed patterns of inflammatory mediators (A-235; B-280; C-210; D-302 signals).
…”
Section: Methodsmentioning
confidence: 99%